Mengembangkan Etika Sosial Antara Siswa dengan Guru dalam Pembelajaran Pendidikan Agama Kristen Sistem Daring - Thomson Siallagan (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
Abstract During the 19th pandemic, the face-to-face learning system turned into a distance learning system. Children learn from home and teachers teach using the internet network. Various problems arise in this online learning system, including problems of social ethics between students and teachers. This study aims to examine how to develop social ethics between students and teachers in online learning during a pandemic. The research method used is the literature review method using literature related to the subject of study. The results of the study found in developing social ethics between students and teachers in online learning during the pandemic are as follows: developing social ethics between students and teachers in participatory learning. Teachers, especially BP teachers, socialize the social ethic repeatedly with a collaborative system, which involves all education stakeholders, including parents and school committees. Teachers are gentle but firm in carrying out these social ethics. Teachers deal with students who lack ethics wisely and on the other hand, teachers are professional and become role models of social ethics in learning.